A Sting Operation: Risk Assessment and Venom Expenditure by Arizona Bark Scorpions (Centruroides sculpturatus) in a Defensive Context - Lindsay A. Marston; Gerad A. Fox; Kim Y. Hung; Shannon J. Delo; William K. Hayes (Toxins)
Scorpion antipredator behavior incorporates risk assessment that informs decision-making and venom usage. We quantified antipredator behaviors of the clinically significant Arizona bark scorpion (Centruroides sculpturatus) in their natural environment using exposure to two stimuli: a freshly thawed laboratory mouse (Mus musculus) and a membrane-covered glass beaker. We videotaped and compared envenomation behaviors between sexes (females, gravid females, and males), across sizes, and between animal orientations (on vertical or horizontal substrates). Results failed to show consistent support for any of our four hypotheses. Females (especially gravid females) were no more likely than males to exhibit higher levels of stinging and venom expenditure. Scorpions on horizontal surfaces compared to those on vertical surfaces, and larger scorpions compared to smaller ones, were likewise no more likely to exhibit higher levels of responsiveness. Mice were more likely to be stung than the membrane-covered beaker, but with fewer and briefer stings, suggesting the scorpions did not attempt to deliver more venom into the mice. Thus, we discerned no clear patterns in risk assessment, stinging, and venom use associated with sex, substrate orientation, body size, or threat stimuli. These findings contrasted with those of several prior laboratory studies. Variation from unaccounted environmental variables may have obfuscated divergent behavioral tactics. Nevertheless, the behaviors we document here provide insights on the range of defensive behaviors exhibited by C. sculpturatus under natural environmental conditions, including the frequency of dry stings (11.8%) to the membrane-covered beakers.